Index Modulation for 5G Wireless Communications - Wen, Miaowen; Cheng, Xiang; Yang, Liuqing; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a thorough examination of index modulation, an emerging 5G modulation technique. It includes representative transmitter and receiver design, optimization, and performance analysis of index modulation in various domains. First, the basic spatial modulation system for the spatial domain is introduced. Then, the development of a generalized pre-coding aided quadrature spatial modulation system as well as a virtual spatial modulation system are presented. For the space-time domain, a range of differential spatial modulation systems are examined, along with the pre-coding design. Both basic and enhanced index modulated OFDM systems for the frequency domain are discussed, focusing on the verification of their strong capabilities in inter-carrier interference mitigation. Finally, key open problems are highlighted and future research directions are considered. Designed for researchers and professionals, this book is essential for anyone workingin communications networking, 5G, and system design. Advanced-level students of engineering and computer science interested in efficiency techniques will also find the content valuable.
Introduction -- Space-Domain Index Modulation -- Space-Time Domain Index Modulation -- Frequency Domain Index Modulation -- Conclusions and Future Directions.
Keywords: Signal processing; Computer networks .; Telecommunication; Signal, Speech and Image Processing; Computer Communication Networks; Communications Engineering, Networks